The role of Xuanfei Zhisou mixture plus fluticasone propionate suspension in the treatment of variant cough in children and its effect on serum amyloid A and c-reactive protein - Zhang, Ying; Song, Yajun; Xue, Jinling; Xue, Ningning (Frontiers in Medicine, 2025)
BackgroundAlbeit fluticasone propionate suspension is effective in treating variant cough in children, there is limited research on the use of Xuanfei Zhisou mixture, and even fewer studies on its combination application. This study aimed to estimate the role of Xuanfei Zhisou mixture (XZM) plus fluticasone propionate suspension (FPS) in the treatment of cough variant in children.Methods122 children with variant cough from March 2020 to May 2023 were classified into observation therapy (XZM + FPS, n = 60) and control therapy (FPS, n = 60) using block randomization. The clinical effect, inflammatory factor, pulmonary function, peripheral eosinophil count, daytime and nighttime cough scores, immune function and untoward reactions were contrasted in two groups.ResultsThe clinical effect, Forced Vital Capacity (FVC), FEV1 (Forced Expiratory Volume)/FVC, CD3+, CD4+ as well as CD4+/CD8+ of the observation therapy were higher than control therapy. After treatment, interleukin-4 (IL-4), tumor necrosis factor-α (TNF-α), serum amyloid A (SAA), c-reactive protein (CRP), eosinophil count as well as daytime and nighttime cough scores in observation therapy were lower than control therapy. Howbeit, there was no diversity in untoward reactions between the two groups.ConclusionXuanfei Zhisou mixture plus FPS had conspicuous role in children with variant cough, which assisted in diminishing cough symptoms, raising pulmonary function, reduce inflammatory factor level and upgrading immune function of children.